Consumer price index manual : theory and practice - International Monetary Fund; International Labour Office (Geneva ; [Great Britain] : International Labour Office, 2004)
The book measures the rate at which the prices of consumer goods and services are changing over time. It is a key statistic for purposes of economic and social policy-making, especially monetary policy and social policy and has substantial and wide-ranging implications for governments, businesses and workers, as well as households.
Formerly CIP.
Includes bibliographical references and index.
usc 03/11/2021
Ref.
Keywords: Consumer price indexes; Prices